Peran Kecintaan Merek Sebagai Pemediasi Antara Pengalaman Merek dan Kepuasan Merek Terhadap Loyalitas Merek Qris - Andriani, Tri; Halimatussaddiah Marpaung (Journal of Trends Economics and Accounting Research, 2024)
The purpose of this study was to analyze the role of brand love as a mediator between brand experience and brand satisfaction on brand loyalty to Qris products in Asahan. This research is descriptive quantitative with survey method. The population in this study were Qris customers in Asahan. The sample used in this study amounted to 280 people. The data analysis tool used is SEM PLS. Brand experience and brand satisfaction have a positive effect on brand love and customer loyalty. Brand love affects brand loyalty. Brand loyalty is a mediator between brand experience and brand satisfaction on brand loyalty. This study extends previous research by examining factors affecting brand loyalty by adding the variable of brand satisfaction and making product love a mediator between brand experience and satisfaction on loyalty to Qris.